The Act 19.223 in general and the hacking crime in particular - Moscoso, Romina (Revista Chilena de Derecho y Tecnología, 2014)
The present paper studies the content that must be given to the category titled as informatics crimes. Confidentiality is proposed as the legal asset that allows to unit all crimes harmful to the logic support of an automatic information treatment system, delimiting the material object over which they relapse. It analyzes the form of subjective commission of the informatics crimes, to then pass to the study of the regulation that Act 19.223 introduces. In another way, it exposes about actual regulation of the legal classification of non-authorized access to an information treatment system, applying the legal asset established in the informatics crimes in general. Also, it resorts to the objective imputation model to determine which behaviors will be criminally relevant of all those that, eventually, could fit in the objective legal description established in the act. Then, it tries to precise the meaning of the intention of to take control, use or know the information contained in the information treatment system. Some concurred figures that could be verified in the practice and the way of solved it are revised and it includes an analysis of comparative law. It finalizes with commentaries of jurisprudence concerning to the exposed theme.